2019
DOI: 10.24903/sj.v4i2.332
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use, Reading Habit and Reading Ability of Students of Private Junior High Schools in Kecamatan Ilir Timur II Palembang

Abstract: This study is aimed to find out whether or not (1) there is any significant correlation between reading ability and reading habit, (2) There is any significant correlation between reading ability and internet use, (3) There is any significant correlation among reading ability, internet use, and reading habit of students of private junior high schools in Kecamatan Ilir Timur II Palembang. The researcher collects the data through 2 instruments namely, reading tests and questionnaires. A test is used to find out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The results of this study, which used data from 256 students at STMIK Sumedang, revealed that there is no connection between students' use of DRs and their reading habits. In a related study, Priambodo et al (2019) used Pearson product-moment correlation to examine students' the Internet use, reading habits, and reading aptitude. 803 students made up the study's population, and 120 students were chosen as the sample size.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of this study, which used data from 256 students at STMIK Sumedang, revealed that there is no connection between students' use of DRs and their reading habits. In a related study, Priambodo et al (2019) used Pearson product-moment correlation to examine students' the Internet use, reading habits, and reading aptitude. 803 students made up the study's population, and 120 students were chosen as the sample size.…”
Section: Literature Reviewmentioning
confidence: 99%